Mean Girls: Adolescent Female Athletes and Peer Conflict in Sport. Issue 1 (2nd January 2016) - Partridge, Julie A.; Knapp, Bobbi A.
Abstract : The purpose of this study was to explore adolescent female athletes' experiences with peer conflict. In-depth, semistructured interviews ( N = 15) were conducted with female athletes participating in high school/club-level sport. Inductive and deductive content analysis was then completed, and 4 distinct themes emerged regarding interpersonal conflict in the sport domain: causes of sport peer conflict, manifestations of sport peer conflict, outcomes of sport peer conflict, and attempts to reduce conflict. Findings imply that sport peer relationships can result in conflict behaviors that are both consistent with developmental literature and distinctive within the adolescent sport domain.